Disaster impacts, resilience, and sustainability opportunities for Gili Trawangan, Indonesia: transdisciplinary reflections following COVID‐19. Issue 2 (29th November 2022) - Partelow, Stefan; Fujitani, Marie; Williams, Sian; Robbe, Delphine; Saputra, Raditya Andrean
Abstract : This paper contains transdisciplinary reflections from both scientists and local NGO (nongovernmental organisation) managers on the international small island tourism destination of Gili Trawangan, Indonesia. These viewpoints centre on the impacts of, as well as the short‐ and long‐term adaptation strategies and sustainability opportunities associated with, two disasters that occurred in rapid succession: the earthquakes that struck Lombok in 2018; and the COVID‐19 pandemic that began in 2020. A brief review of the governance challenges facing Gili Trawangan sets up the analysis of the findings and the presentation of new empirical insights into how the island's communities have dealt with two unique disaster scenarios over the past three years. The paper draws on a community resilience framework premised on social capital and collective action theories to position the island's ability to transition towards sustainable tourism in the wake of the COVID‐19 pandemic. It concludes by laying out sustainability opportunities going forward. نبذة مختصرة: يوفر هذا المقال تأملات متعددة الاختصاصات من علماء ومديري منظمات محلية غير حكومية على الوجهة السياحية الدولية لجزيرة جيلي تروانجان الصغيرة بإندونيسيا فيما يتعلق بآثار واستراتيجيات التكيّف على المدى الطويل وفرص الاستدامة من كارثتين حدثتا على تتابع سريع: زلزال لومبوك عام 2018 وجائحة كوفيد‐19 التي بدأت عام 2020. تضع مراجعة موجزة لتحديات الحوكمة في الجزيرة تحليلنا للنتائج المعاد النظر فيها ورؤى تجريبية جديدة عن كيفية تعامل مجتمعات الجزيرة مع سيناريوهيْن فريديْن للكوارث على مدى السنوات الثلاث الماضية. حيث نعتمد على إطار مرونة المجتمع القائم على رأس المال الاجتماعي ونظريات العمل الجماعي لوضع قدرة الجزيرة على الانتقال نحو السياحة المستدامة بعد الوباء. وأخيراً نختتم بفرص الاستدامة التي تمضي قدماً. الكلمات المفتاحية: رأس المال، عمل جماعي/ مشترك، مجتمع محلي، كوفيد‐19، زلزال، جزيرة، جنوب شرق آسيا، السياحة، التحول 摘要: 本文提供了科学家和当地非政府组织（NGO）管理人员对国际旅游小岛印度尼西亚吉利特拉旺安的跨学科反思，内容为：接连发生的两起灾害（2018年的的龙目岛地震和2020年爆发的新冠肺炎疫情）对该岛带来的影响、短期和长期适应策略和可持续发展机会。我们通过对该岛面临的治理挑战的简要综述建立了分析，内容为过去三年岛上的社群如何处理两个罕见的灾难状况的相关旧成果和新见解。我们基于社会资本和集体行动理论绘制出了社群抗灾害能力框架，并且以此定位该岛在后疫情时代向可持续旅游业过渡的能力。最后，我们以未来的可持续发展机会作结论。 关键词：资本；集体行动；社群；新冠肺炎；地震；岛屿；社会资本；东南亚；旅游业；转型